Hubungan Dukungan Keluarga Terhadap Efikasi Diri Ibu Menyusui Dalam Memberikan ASI Eksklusif Di Puskesmas Sumur Batu Kota Bandar Lampung - Ariyanti Wardiyah; Rilyani Rilyani; Adi Ari Zandi (Malahayati Nursing Journal, 2021)
ABSTRACT: THE RELATIONSHIP ON FAMILY SUPPORT ON THE SELF EFFICATION OF BREASTFEEDING MOM IN GIVING EXCLUSIVE ASSET AT PUSKESMAS SUMUR BATU, BANDAR LAMPUNG CITY Introduction: The coverage of infants receiving exclusive breastfeeding in Lampung Province in 2018 according to Riskesdas was 32.2%, where this figure is below the coverage in Indonesia and still below the expected target of 80%. The percentage of babies who were exclusively breastfed in Bandar Lampung City in 2016 was 53.46% (3,938 of 7,366 babies). The lowest achievement of exclusive breastfeeding is Puskesmas Sumur Batu at 40.1%. One of the factors of exclusive breastfeeding is self-confidence. If the mother has low self-confidence, her milk production will decrease. The factors that influence self-confidence include personality, environment, and attitudes.Purpose: The research objective was to determine the relationship between family support and self-efficacy of breastfeeding mothers in giving exclusive breastfeeding at Sumur Batu Health Center, Bandar Lampung City, in 2021.Methods: This type of research is quantitative with a cross-sectional design. The study population was mothers who had children aged 6-12 months in the Sumur Batu Health Center, Bandar Lampung City. A total of 214 people. Sample of 69 respondents. The data collection tool used in this study was a questionnaire. The statistical test used was the chi-square test with the help of a computer.Results: The frequency distribution of respondents with unsupportive families were 36 respondents (52.2%), respondents had low self-efficacy, namely 50 respondents (72.5%), There was a relationship between family support and the self-efficacy of breastfeeding mothers in giving exclusive breastfeeding at Sumur Batu Health Center Bandar Lampung City in 2019 (p value 0.011).Conclusion: There is a relationship between family support and self-efficacy of breastfeeding mothers in providing exclusive breastfeeding at Sumur Batu Health Center Bandar Lampung City in 2019Suggestion: The results of this study suggest breastfeeding mothers be confident in their ability to breastfeed their babies because breast milk is the best food for babies Keywords: Family Support, Self Efficacy, Exclusive BreastfeedingINTISARI: HUBUNGAN DUKUNGAN KELUARGA TERHADAP EFIKASI DIRI IBU MENYUSUI DALAM MEMBERIKAN ASI EKSKLUSIF DI PUSKESMAS SUMUR BATU KOTA BANDAR LAMPUNG TAHUN 2021  Pendahuluan: Cakupan bayi mendapatkan ASI Ekslusif di Provinsi Lampung tahun 2018 menurut Riskesdas sebesar 32,2%, dimana angka ini di bawah cakupan di Indonesia dan masih di bawah target yang diharapkan yaitu 80%. Persentase bayi yang mendapat ASI ekslusif di Kota Bandar Lampung pada tahun 2016 sebesar 53.46% (3.938 dari 7.366 bayi). Capaian ASI ekslusif yang terendah adalah Puskesmas Sumur Batu sebesar 40,1%. Salah satu faktor pemberian ASI eksklusif yaitu kepercayaan diri. Jika ibu memiliki kepercayaan diri yang rendah maka produksi ASI-nya akan menurun. Faktor-faktor yang mempengaruhi kepercayaan diri yaitu meliputi kepribadian, lingkungan, dan sikap.Tujuan: Tujuan penelitian adalah untuk mengetahui hubungan dukungan keluarga terhadap efikasi diri ibu menyusui dalam memberikan ASI Eksklusif di Puskesmas Sumur Batu Kota Bandar Lampung Tahun 2021. Metode: Jenis penelitian ini adalah kuantitatif dengan rancangan cross sectional. Populasi penelitian adalah ibu yang memiliki balita usia 6-12 bulan di Wilayah Kerja Puskesmas Sumur Batu Kota Bandar Lampung. Sejumlah 214 orang. Sampel 69 responden. Alat pengumpulan data yang digunakan dalam penelitian ini berupa kuesioner. Uji statistik yang digunakan adalah uji chi square dengan bantuan komputer.Hasil:  Distribusi frekuensi responden dengan keluarga tidak mendukung yaitu sebanyak 36 responden (52.2%), responden memiliki efikasi diri yang rendah yaitu sebanyak 50 responden (72.5%), Ada hubungan dukungan keluarga terhadap efikasi diri ibu menyusui dalam memberikan ASI Eksklusif di Puskesmas Sumur Batu Kota Bandar Lampung Tahun 2019 (p value 0,011).Kesimpulan: Ada hubungan dukungan keluarga terhadap efikasi diri ibu menyusui dalam memberikan ASI Eksklusif di Puskesmas Sumur Batu Kota Bandar Lampung Tahun 2019Saran: Hasil penelitian ini menyarankan kepada ibu menyusui untuk yakin akan kemampuannya dalam menyusui bayi karena ASI merupakan makanan terbaik untuk bayi Kata Kunci : Dukungan Keluarga, Efikasi Diri, ASI Eksklusif